Application of Temperature-Dependent Fluorescent Dyes to the Measurement of Millimeter Wave Absorption in Water Applied to Biomedical Experiments - Nataliia Kuzkova; Oleksandr Popenko; Andrey Yakunov (International Journal of Biomedical Imaging)
Temperature sensitivity of the fluorescence intensity of the organic dyes solutions was used for noncontact measurement of the electromagnetic millimeter wave absorption in water. By using two different dyes with opposite temperature effects, local temperature increase in the capillary that is placed inside a rectangular waveguide in which millimeter waves propagate was defined. The application of this noncontact temperature sensing is a simple and novel method to detect temperature change in small biological objects.